A role for an HTLV-1 vaccine? - Ratner, Lee (Frontiers in Immunology, 2022)
HTLV-1 is a global infection with 5-20 million infected individuals. Although only a minority of infected individuals develop myelopathy, lymphoproliferative malignancy, or inflammatory disorders, infection is associated with immunosuppression and shorter survival. Transmission of HTLV-1 is through contaminated blood or needles, and sexual intercourse. HTLV-1 is a delta retrovirus that expresses immunogenic Gag, Envelope, Tax, and Hbz proteins. Neutralizing antibodies have been identified directed against the surface envelope protein, and cytotoxic T-cell epitopes within Tax have been characterized. Thus far, there have been few investigations of vaccines directed against each of these proteins, with limited responses, thus far. However, with new technologies developed in the last few years, a renewed investigation is warranted in search for a safe and effective HTLV-1 vaccine.